Minor procedure, major impact: Patient-reported outcomes following urethral meatotomy. Issue 2 (April 2018) - Varda, Briony K.; Logvinenko, Tanya; Bauer, Stuart; Cilento, Bartley; Yu, Richard N.; Nelson, Caleb P.
Summary: Introduction: Urethral meatotomy as treatment for meatal stenosis is a common pediatric urology procedure; however, little is known about the patient experience following this procedure. Objective: We aim to evaluate clinical factors associated with patient-reported symptom improvement after urethral meatotomy. Study design: The families of boys undergoing urethral meatotomy between 2/2013 and 8/2016 received a survey by mail 6 weeks after surgery. Families were queried on changes in symptoms using a Likert-type scale (5 = much improved, 4 = somewhat improved, 3 = no change, 2 = somewhat worse, and 1 = much worse). Patient and procedure characteristics of the respondents were obtained via chart review. These included surgical indication(s) (abnormal stream, dysuria, or storage symptoms), postoperative complications, reoperation, and unplanned postoperative communications. Patients who had procedures other than simple urethral meatotomy were excluded. Descriptive statistics were compiled, and generalized estimating equations used to determine the associations of patient and procedure characteristics with symptom improvement. Results: We sent 629 surveys and received 194 responses (30.4%). Twelve respondents were excluded for complex procedures or miscoding. The majority of respondents were privately insured (74%) and were between 5 and 12 years old (45%) or 1 and 4 years old (42%). The most frequent surgical indication was abnormal stream (72%) followed by pain (21%) and storage symptoms (15.5%). Nine respondents had minor complications (4.9%). Four patients had restenosis requiring repeat urethral meatotomy. After surgery, a majority (79%) were "much improved, " 16% were "somewhat improved, " 3% had "no change, " and 1% were "somewhat worse." No family reported "much worse." Those patients who had "abnormal stream" as a surgical indication were significantly more likely to report "much improved" (OR 1.83, p = 0.014) than those without. Patient-reported improvement was not associated with suture use, patient age, insurance, surgeon, or location of the procedure (Table). Discussion: Little has been written about patient-reported outcomes following urethral meatotomy. Our study affirms that the majority of boys improve following this procedure. However, improvement is significantly more likely if the child has a preoperative indication of an abnormal stream, such as deflection or spraying. Boys with symptoms of dysuria, frequency, or incontinence may be experiencing sequelae of meatal stenosis that simply take longer to improve. Alternatively, the meatal stenosis may be incidental to the primary symptoms. Conclusions: A majority of families report substantial symptomatic improvement after urethral meatotomy. However, boys undergoing urethral meatotomy for reasons other than a urinary stream abnormality are less likely to experience improvement. Table Patient characteristics and key outcomes stratified by patient-reported improvement. Not "much improved" "Much improved" p -value ( n = 38) ( n = 144) Patient characteristics Indication ( n ; %) Stream abnormality 26/141 (18.4%) 115/141 (81.6%) 0.014 ∗ Pain 11/41 (26.8%) 30/41 (73.2%) 0.40 Storage symptoms 6/30 (20.0%) 24/30 (80.0%) 0.90 Suture used ( n ; %) 25/131 (19.1%) 106/131 (80.9%) 0.21 Outcomes Complications 5/9 (55.6%) 4/9 (44.4%) 0.02 ∗ Reoperation 3/4 (75.0%) 1/4 (25.0%) 0.02 ∗ ∗ A p -value <0.05 was considered significant.